Comparative studies on reproductive traits of natural populations of Eisenia andrei Bouché, 1972 from Zagros Mountain, Iran (Annelida: Oligochaeta) - Latif, Robabeh; Malek, Masoumeh; Aminjan, Atabak Roohi; Nadimoghadam, Nasim; Mirshamsi, Omid; Mirmonsef, Hassan; Hosseini, Elham (Zootaxa, 2018)
Comparative studies were carried out on growth and reproduction patterns of eight populations of Eisenia andrei (Bouché, 1972) from different parts of western Iran along the Zagros Mountains, considered to lie within the natural range of this species. Parameters were gain in body weight, number of cocoon production, hatching success, number of hatchlings, hatchlings growth and survival. There were significant differences in mean numbers of viable cocoons, incubation time, reproductive rate, growth rate and final weight between different populations. The resulting groupings did only partially coincide with genetic clusters established in a previous study. It is nonetheless suggested to include life cycle parameters as an additional set of data to understand the micro-taxonomic structure of variable species.